2022
DOI: 10.1186/s12967-022-03421-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutation patterns and circulating tumour DNA-derived prognostic markers in advanced breast cancer patients

Abstract: Background The correlations between circulating tumour DNA (ctDNA)-derived genomic markers and treatment response and survival outcome in Chinese patients with advanced breast cancer (ABC) have not been extensively characterized. Methods Blood samples from 141 ABC patients who underwent first-line standard treatment in Peking University Cancer Hospital were collected. A next-generation sequencing based liquid biopsy assay (PredicineCARE) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…Consistent with previous studies 22 , 23 , TP53 and PIK3CA mutations were the two most altered genes. It is well known that the frequency of TP53 mutation is especially high in HER2 + breast cancer, and TP53 mutation per se is associated with early onset breast cancer and poor prognosis 24 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies 22 , 23 , TP53 and PIK3CA mutations were the two most altered genes. It is well known that the frequency of TP53 mutation is especially high in HER2 + breast cancer, and TP53 mutation per se is associated with early onset breast cancer and poor prognosis 24 .…”
Section: Discussionsupporting
confidence: 92%
“…ctDNA is assumed to reflect the tumor burden and has been suggested as a tool for prognostication and follow-up in patients with advanced cancers 30 , 31 . Several studies have shown the prognostic ability of ctDNA fractions in patients with MBC 22 , 23 , and a recent study advocated its role as a pragmatic, independent prognostic biomarker across the four most common advanced cancer types, including MBC, in real-world settings 32 . Moreover, although not addressed in our study, several studies have found that early on-treatment ctDNA dynamics were a surrogate for treatment outcomes 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…They also found that PIP-positive cells were characterized by increased expression of several genes with the pro-apoptotic function ( BAD , CDKN2A , PRAME ), but also concomitant up-regulation of genes involved in the inhibition of cell growth and proliferation, and down-regulation of genes promoting cell proliferation. Two of these pro-apoptotic genes ( BAD and CDKN2A ) were also associated with drug resistance of BC cells 49 52 . However, they were different from the genes that we identified.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies evaluating the clinical validity of ctDNA dynamics for intercepting resistance are reported in Table 3 [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Most of them evaluated ctDNA through a targeted approach, confirming the known evidences about resistance to endocrine therapy, CDK4/6-inhibitors, PIK3CAinhibitors and antihuman epidermal growth factor receptor 2 (HER2) drugs.…”
Section: Clinical Validitymentioning
confidence: 78%